Performance of Goats Fed Moringa oleifera Leaf Meal Incorporated in Concentrate Mixture - Ali, Syed Bilal; Kawitkar, S.B.; Deshmukh, A.D.; Dhok, A.P.; Jawale, M.R.; Chopde, S.V.; Parihar, N.B. (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to assess the growth performance of goats fed Moringa oleifera leaf meal incorporated in concentrate mixture for 90 days. Twelve goats were divided into 2 groups of 6 animals each. The animals in group T0 (control) received a concentrate mixture containing cotton seed cake (CSC) alongwith ad lib. fodder whereas in group T1, 50% of CSC proportion in concentrate mixture was replaced by M. oleifera leaf meal. The values for average DM intake, feed conversion ratio and digestibility of nutrients (DM, CP, EE and CF) were similar in two groups whereas NFE digestibility was significantly (P